parenting support - Mazzucchelli, Trevor; Wilker, Lienke; Sanders, Matthew (2019)
Of all the potentially modifiable environmental risk and protective factors that can meaningfully influence children’s development, none is more important than the quality of parenting children receive. The influence of parenting on children’s development is pervasive, affecting aspects as diverse as the child’s cognition, language, emotion regulation, social skills, peer relationships, and physical and mental health. This chapter explores the challenges faced by families raising a child with an intellectual disability to provide the context and a rationale for the provision of parenting support to parents and carers of children with an intellectual disability. A brief history of parent support in the disability field is provided before a range of contemporary evidence-based parenting support programs are reviewed. There is considerable evidence supporting the efficacy and effectiveness of parenting interventions based on social learning theory principles; however, these interventions reach too few families. An argument for an all of population approach to parenting support for families with a child who has a disability is presented. A model for what a population approach might look like is described, along with evidence to show that such an approach is both feasible and effective. Challenges in implementing population approach and future directions for the field are provided.